An audit of emergency medicine responses to children injured in violence. Issue 2 (15th February 2010) - Shepherd, Jonathan; Tuthill, David; Parry, Bethan; Dowd, Hugo
Abstract : Aim: To audit emergency department (ED) responses to violence in which children are injured in violence in a European capital city. Methods: A prospective survey of children (aged <16 years) was conducted in Cardiff's only ED using ED software adapted for this purpose. All clinical records were scrutinised for evidence of discussion with and referral to agencies concerned with child protection. Results: 123 children reportedly injured in violence (92 boys) were treated in 2004, six aged 5–9  years; one under 5 years. Overall, 24 (19%) incidents had been reported to the police prior to ED arrival. Only four (3%) prompted documented referral or discussions with other agencies while in the ED. 78% prompted no action apart from treatment of injuries. 13 (10%) children had fractures or were admitted, but only two of these incidents had been drawn to police attention. Only five (4%) were injured at home; a large majority were injured in the street or at school with fists or feet (12 with a weapon) by other children or adults. Conclusions: In this audit, most violence in which children were injured took place in schools and in the street. For children of secondary school age, ED treatment rarely prompted referral or discussion with agencies responsible for child safety. Particularly since youth and child violence are major national issues, policy and practice in this area were developed and built on disclosure of all such cases to a single referral point in the local authority education department.